Vector control at the household level: an analysis of its impact on women - Winch, Peter J; Lloyd, Linda S; Hoemeke, Laura; Leontsini, Elli (Acta tropica, 1994)
The home is the setting where many vector-borne diseases are transmitted. Strategies for their control consequently have to involve the active participation of householders. In this paper we propose that low rates of participation in control activities frequently are related to the negative impact they have on women's power and authority within the domestic domain. This can arise from intrusion into domestic space by male vector control personnel, reorganization of the domestic environment as part of control activities, and promulgation of the idea that disease originates from within the home. In addition, women may need to make significant investments of both time and money in order to carry out the recommended control measures. Very little is known about the impact of vector control measures on women. This subject will assume increasing relevance as planners seek to involve householders, rather than the personnel of vertically-organized control programmes, in the implementation of vector control measures.